PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN BOGOR - Muchammad Hamdani; Syaiful Anwar; Muhammed Raihan Aulia (Economicus : Jurnal Ekonomi dan Manajemen, 2026)
This study aims to determine the effect of motivation and work discipline on performance Knowing the Effect of Motivation and Discipline on Employee Performance at the Public Works and Spatial Planning Agency of Bogor Regency. The type of research used is causality with a quantitative approach, the location of the research is at the Office of Public Works and Spatial Planning of Bogor Regency. The research population at the Office of Public Works and Spatial Planning of Bogor Regency with the Krejcie & Morgan theory is a total of 253 personnel and 152 samples.In the results of the study showed that Motivation will decrease Performance by 0.265 and Discipline will increase performance by 0.589 simultaneously have an Influence on the performance of the Public Works and Spatial Planning Agency of Bogor Regency, this is proven based on the results of the F test (simultaneous) obtained F value calculated greater than F Table, F calculated 77.712> F Table 2.34. Based on the results of the Coefficient of Determination test obtained Adjusted R Square value of 0.499 or 49.9%. This shows that Motivation and Discipline simultaneously contribute to influencing Performance. While the remaining 50.1% is influenced by other factors that are not discussed or examined in the study.